Withaferin A inhibits Chikungunya virus nsP2 protease and shows antiviral activity in the cell culture and mouse model of virus infection. - Kiran Bala Sharma; Chandru Subramani; Khashpatika Ganesh; Anshula Sharma; Brohmomoy Basu; Shivani Balyan; Ghanshyam Sharma; Shouri Ka; Arundhati Deb; Mitul Srivastava; Saurabh Chugh; Sapna Sehrawat; et al. (PLoS Pathogens)
Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus causing fever, myalgia, and debilitating joint swelling and pain, which in many patients becomes chronic. The frequent epidemics of CHIKV across the world pose a significant public health burden necessitating the development of effective antiviral therapeutics. A cellular imaging-based high-content screening of natural compounds identified withaferin A (WFA), a steroidal lactone isolated from the plant Withania somnifera, as a potent antiviral against CHIKV. In the ERMS cells, WFA inhibited CHIKV replication early during the life cycle by binding the CHIKV non-structural protein nsP2 and inhibiting its protease activity. This inhibited the viral polyprotein processing and the minus-sense viral RNA synthesis. WFA mounted the nsP2 protease inhibitory activity through its oxidising property as the reducing agents N-acetylcysteine and Glutathione-monoethyl ester effectively reversed the WFA-mediated protease inhibition in vitro and abolished the WFA-mediated antiviral activity in cultured cells. WFA inhibited CHIKV replication in the C57BL/6 mouse model of chikungunya disease, resulting in significantly lower viremia. Importantly, CHIKV-infected mice showed significant joint swelling which was not seen in WFA-treated mice. These data demonstrate the potential of WFA as a novel CHIKV antiviral.